Comparing thoracoabdominal injuries of manual versus load-distributing band cardiopulmonary resuscitation. (June 2020) - Sonnemans, Lianne J.P.; Bayat, Alireza R.; Bruinen, Aniek R.C.; van Wely, Marleen H.; Brouwer, Marc A.; Bosboom, Dennis; van der Hoeven, Johannes G.; Prokop, Mathias; Klein, Willemijn M.
Abstract : Objective: To identify and compare manual and load-distributing band (LDB) cardiopulmonary resuscitation (CPR)-related injuries. Methods: Retrospective observational cohort study. Adult, nontraumatic deaths with a postmortem computed tomography scan (PMCT) performed were classified into two groups: deceased after LDB CPR or after manual CPR. PMCT scans were reviewed for thoracoabdominal injuries such as fractures, pneumothorax and hemorrhage. The injuries between groups were compared. Results: LDB CPR ( n  = 43) showed increased incidences of posterior rib fractures (53 vs 18%, P  = 0.006), pneumothorax (23 vs 4%, P  = 0.04) and more pericardial fluid (median 12  vs 6 mm, P  = 0.002) compared with manual CPR ( n  = 29). Multivariable regression analysis revealed that LDB CPR was significantly associated with posterior rib fractures [odds ratio (OR) 5.37, 95% confidence interval (CI): 1.44–20.09, P  = 0.01). Pneumothorax (OR 6.80, 95% CI: 0.73–62.99, P  = 0.09) and the amount of pericardial fluid (OR 3.40, 95% CI: 0.20–56.32) were not significantly associated with LDB CPR. No significant difference was found for anterolateral rib fractures, sternal fractures, vertebral fractures, pleural fluid, hemothorax, hemopericardium, pneumoperitoneum, perihepatic, perisplenic and perirenal hemorrhage. Conclusion: Rib fractures, sternal fractures, hemothorax and hemopericardium are common CPR-related injuries. LDB CPR is significantly associated with more posterior rib fractures and a trend toward more pneumothoraces is observed when compared with manual CPR. This knowledge is important for caretakers in the case of ongoing CPR, as a pneumothorax may attribute to not achieving persistent return of spontaneous circulation, and to improve postresuscitation care of survivors.